E-Marketplace Brand Equity: A Study on Generational Cohort - Yan Enggal Asmara; Albert Kriestian Novi Adhi Nugraha (Journal of Management and Entrepreneurship Research, 2025)
Objective: This study examines generational differences in e-marketplace brand equity (eMBE) across Generation Y and Z, and compares the platforms Tokopedia and Shopee. Research Design & Methods: A quantitative approach was employed through surveys, in which respondents assessed the dimensions of eMBE by filling out a self-administered questionnaire. This study utilized quota sampling and ANOVA tests for data analysis. Findings: Significant differences were observed in emotional connection and trust between generations, with Generation Z rating emotional connection higher than Generation Y. Trust differences arose from varying perceptions of risk, with Generation Y expressing greater concern. In terms of platform comparisons, differences in online experience, trust, and fulfillment were noted, with Tokopedia receiving higher ratings despite its smaller market share. No significant differences were found in responsive service nature or green dedication across generations or platforms. Implications and Recommendations: The findings indicate that emotional connection is a key factor for Generation Z, while Generation Y places more emphasis on trust. Tokopedia’s superior ratings in online experience and fulfillment suggest it holds potential to challenge Shopee’s market leadership. Both platforms should enhance responsiveness and emphasize green initiatives to align with consumer concerns. Social Implications: This study promotes eMBE as a tool to encourage better services and sustainable practices. Contribution & Value Added: This research provides insights into the role of generational and platform-specific factors in shaping eMBE. It offers strategic guidance for e-marketplaces to refine their customer engagement and trust-building approaches.